The prognostic significance of cancer-associated fibroblasts in pancreatic ductal adenocarcinoma - Hyunjin Park; Yangkyu Lee; Hyejung Lee; Jin-Won Kim; Jin-Hyeok Hwang; Jaihwan Kim; Yoo-Seok Yoon; Ho-Seong Han; Haeryoung Kim (Tumor Biology, 2017)
Cancer-associated fibroblasts are abundant in the desmoplastic stroma of pancreatic ductal adenocarcinomas and are considered to play important roles in tumor progression. In this study, we investigated the expression status of secreted protein acidic and rich in cysteine, periostin, fibroblast-activated protein, and the newly developed proCOL11A1 antibody in the stroma of surgically resected pancreatic ductal adenocarcinomas and their prognostic implications. Tissue microarrays were constructed from 155 surgically resected pancreatic ductal adenocarcinomas and paired non-neoplastic pancreata and from another independent set of 48 normal/benign pancreata, and immunohistochemical stains were performed for proCOL11A1, fibroblast-activated protein, secreted protein acidic and rich in cysteine, and periostin. The immunohistochemical stain results were correlated with clinicopathological features and survival data. proCOL11A1, fibroblast-activated protein, secreted protein acidic and rich in cysteine, and periostin expression was significantly increased in the intratumoral stroma of pancreatic ductal adenocarcinomas compared to paired non-neoplastic pancreata (proCOL11A1: 145/155 (93.5%) vs 26/154 (16.9%); fibroblast-activated protein: 139/143 (97.2%) vs 82/132 (62.1%); secreted protein acidic and rich in cysteine: 113/150 (75.3%) vs 49/132 (37.1%); periostin: 135/151 (89.4%) vs 45/135 (33.3%); p < 0.001, all). While the four markers were expressed at lower levels in normal/benign pancreata, there were no significant differences in the expression frequencies among normal pancreas, acute pancreatitis, and chronic pancreatitis. Interestingly, on survival analysis, low intratumoral fibroblast-activated protein + cancer-associated fibroblast counts (<100/high-power field) were associated with a significantly reduced overall survival compared to those with high fibroblast-activated protein + cancer-associated fibroblast counts (p = 0.010; hazard ratio 5.2 (95% confidence interval 1.3–21.3)). Similar patterns were seen for proCOL11A and secreted protein acidic and rich in cysteine and overall and disease-free survival, although not statistically significant. In conclusion, we demonstrate that the presence of cancer-associated fibroblasts in the tumor stroma may not always be associated with a poor prognosis as suggested in many studies; on the contrary, it may even be associated with prolonged survival, supporting the recent experimental findings that tumor stroma may have a protective role rather than enhance aggressive behavior.